Long‐term Retention of Cardiopulmonary Resuscitation Skills After Shortened Chest Compression–only Training and Conventional Training: A Randomized Controlled Trial. (January 2014) - Nishiyama, Chika; Iwami, Taku; Kitamura, Tetsuhisa; Ando, Masahiko; Sakamoto, Tetsuya; Marukawa, Seishiro; Kawamura, Takashi; Gratton, Matthew
Abstract Objectives It is unclear how much the length of a cardiopulmonary resuscitation (CPR) training program can be reduced without ruining its effectiveness. The authors aimed to compare CPR skills 6 months and 1 year after training between shortened chest compression–only CPR training and conventional CPR training. Methods Participants were randomly assigned to either the compression‐only CPR group, which underwent a 45‐minute training program consisting of chest compressions and automated external defibrillator (AED) use with personal training manikins, or the conventional CPR group, which underwent a 180‐minute training program with chest compressions, rescue breathing, and AED use. Participants' resuscitation skills were evaluated 6 months and 1 year after the training. The primary outcome measure was the proportion of appropriate chest compressions 1 year after the training. Results A total of 146 persons were enrolled, and 63 (87.5%) in the compression‐only CPR group and 56 (75.7%) in the conventional CPR group completed the 1‐year evaluation. The compression‐only CPR group was superior to the conventional CPR group regarding the proportion of appropriate chest compression (mean ± SD = 59.8% ± 40.0% vs. 46.3% ± 28.6%; p = 0.036) and the number of appropriate chest compressions (mean ± SD = 119.5 ± 80.0 vs. 77.2 ± 47.8; p = 0.001). Time without chest compression in the compression‐only CPR group was significantly shorter than that in the conventional CPR group (mean ± SD = 11.8 ± 21.1 seconds vs. 52.9 ± 14.9 seconds; p < 0.001). Conclusions The shortened compression‐only CPR training program appears to help the general public retain CPR skills better than the conventional CPR training program.